Mechanical Properties of Corner Lap-45 Types Joined Using Friction Stir Welding - Setiawan, Widia; Santoso, Nugroho; Winarto, Felixianus Eko Wismo; Krisnaputra, Radhian; Mandala, Wirawan Widya; Maulana, Jibril (Universitas Negeri Malang, 2024)
Solid welding has always been concerned with probe design, pins, and joint strength. Many researchers have conducted studies on joints, such as butt joints, lap joints, and T joints, but the results show low strength. This study analyzes the mechanical properties of a new design of a 90o angle joint joined by friction stir welding. This study connected aluminum 6061 using the friction stir welding method using a rectifying jig and a probe with EMS 45 material. The corner joint designs used corner-lap 45 with feed rate as independent variables in 6, 8, 10, 15, and 30 mm/min and dependent variable probe rotation speed at 1000 rpm and shoulder pressure in 584 kg. The results show low feed rates create chips and fish fins on the advancing side, and microstructure test results at low feed rates (6-15 mm/min) indicate the presence of interface bonding. The hardness value of the stir zone also shows an insignificant increase. In the tensile test results, the tensile strength decreases from the base metal value, which then the tensile strength increases along with the increase in feed rate up to a feed rate of 15 mm/min and decreases again at a feed rate of 30 mm/min.